Σεξουαλικότητα και ποιότητα ζωής ιδρυματοποιημένων ηλικιωμένων - Αγαθοκλέους, Μαρία (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction: Sexuality is a basic need of human integration. The elderly often have to live in nursing care homes, the need for expression of their sexuality in these conditions is getting difficult. Purpose: Investigate the attitudes and views of older people living in nursing care homes and nurses/carers in relation to sexuality and quality of life and its relation to various factors. Material and Methods: The literature search was made in electronic databases Medline, Pub Med, Cinahl and Google Scholar with the keywords : "sexuality, sexual behavior, nursing home residents, elderly in old homes, elderly, aged, old people" and in all possible combinations by using the AND and OR words from 2002 to 2013. In the present study included 8 articles and 5 literature reviews. Results: The majority of the studies reviewed indicate that the expression of sexuality of older people usually perceived as a behavior problem and not as an expression of a basic human need. Moreover, the presence of cognitive disorders such as dementia, the problem of expressing sexuality becomes even more apparent (p<0.01). Regarding the main factors affecting the attitudes and perceptions of nurses about sexuality of older people at a late stage of their lives, primarily include social stereotypes, religion and level of education (p<0.01). Conclusions: Sexuality is a basic human need therefore continues to exist at all stages of life. What characterizes the sexuality of the elderly is the desire for expression in different ways. The nurses/carers play the most important role in the care of elderly people so it must receive adequate training. However the issue was not exhausted and needs further investigation.
Keywords: Sexuality; Elderly; Dementia; Σεξουαλικότητα; Ηλικιωμένοι; Άνοια